PERAN ANGGARAN KAS DALAM MENJAGA LIKUIDITAS PERUSAHAAN JANGKA PENDEK - Uci Andriani; Aninda Karina Azzahra; Nila Fauziah Napitupulu (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study examines the role of cash budgeting in maintaining short-term company liquidity. The primary objective is to analyze how planning and managing cash budgets can enhance liquidity stability and prevent liquidity risk. The methodology employs a literature review from various academic sources and company practices, utilizing a qualitative analysis approach. The findings indicate that effective cash budgeting enables accurate cash flow forecasting, resource optimization, and reduction of short-term financial uncertainties. Disciplined and planned cash management has been shown to improve a company’s ability to meet short-term obligations on time while strengthening overall financial position. These results highlight the strategic importance of cash budgeting as a vital tool in liquidity management.